Serotonergic Neurons in the Brain and Gnathal Ganglion of Larval Spodoptera frugiperda - Zhang, Jia-Jia; Sun, Long-Long; Wang, Ya-Nan; Xie, Gui-Ying; An, Shi-Heng; Chen, Wen-Bo; Tang, Qing-Bo; Zhao, Xin-Cheng (Frontiers in Neuroanatomy, 2022)
The fall armyworm Spodoptera frugiperda (S. frugiperda) (Lepidoptera: Noctuidae) is a worldwide, disruptive, agricultural pest species. The larvae of S. frugiperda feed on seedling, leave, and kernel of crops with chewing mouthparts, resulting in reduced crop yields. Serotonin is an important biogenic amine acting as a neural circuit modulator known to mediate lots of behaviors including feeding in insects. In order to explore the serotonergic neural network in the nervous system of larval S. frugiperda, we performed immunohistochemical experiments to examine the neuropil structure of the brain and the gnathal ganglion with antisynapsin and to examine their serotonergic neurons with antiserotonin serum. Our data show that the brain of larval S. frugiperda contains three neuromeres: the tritocerebrum, the deutocerebrum, and the protocerebrum. The gnathal ganglion also contains three neuromeres: the mandibular neuromere, the maxillary neuromere, and the labial neuromere. There are about 40 serotonergic neurons in the brain and about 24 serotonergic neurons in the gnathal ganglion. Most of these neurons are wide-field neurons giving off processes in several neuropils of the brain and the gnathal ganglion. Serotonergic neuron processes are mainly present in the protocerebrum. A pair of serotonergic neurons associated with the deutocerebrum has arborizations in the contralateral antennal lobe and bilateral superior lateral protocerebra. In the gnathal ganglion, the serotonergic neuron processes are also widespread throughout the neuropil and some process projections extend to the tritocerebrum. These findings on the serotonergic neuron network in larval S. frugiperda allow us to explore the important roles of serotonin in feeding and find a potential approach to modulate the feeding behavior of the gluttonous pest and reduce its damage.